1996
DOI: 10.1259/0007-1285-69-823-668
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of fetal brain abnormalities using a HASTE sequence

Abstract: HASTE (half-Fourier acquisition single-shot turbo spin echo) is a sequence that enables T2 weighted magnetic resonance (MR) images to be obtained in a few seconds. The purpose of this study was to evaluate the usefulness of this sequence in the diagnosis of fetal cerebral abnormalities. Five fetuses suspected of having cerebral abnormalities on ultrasound examination were studied by MR imaging using the HASTE sequence in utero. We compared the images with post-natal MR images or computed tomography (CT) scans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…To date, 15 studies encompassing 934 fetal MRI cases (including this review) have been reported using scanners at field strengths of 1.5 T or less, and no harmful effects to the developing fetus have been documented. This includes one large study of 400 fetuses, and another involving 20 children with a 3-year follow-up [1, 3, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37]. The second problem, motion artifact, has often been dealt with in the past by the administration of sedatives or paralytics, but the use of these agents obviously increases the complexity and risk of the study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 15 studies encompassing 934 fetal MRI cases (including this review) have been reported using scanners at field strengths of 1.5 T or less, and no harmful effects to the developing fetus have been documented. This includes one large study of 400 fetuses, and another involving 20 children with a 3-year follow-up [1, 3, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37]. The second problem, motion artifact, has often been dealt with in the past by the administration of sedatives or paralytics, but the use of these agents obviously increases the complexity and risk of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the excellent contrast afforded by T2-weighted images between the cerebrospinal fluid and the brain, HASTE imaging shows a great promise in evaluating the fetal brain abnormalities. Several similar cases using the HASTE sequence to diagnose fetal brain abnormalities have been reported recently [10,14,15].…”
Section: Discussionmentioning
confidence: 74%
“…Fetal curarization and/or maternal sedation before the examination is usually needed to eliminate motion artifacts [11][12][13]. However, the recently developed fast scanning techniques provide clear images in single-breath hold without premedication [10,14,15]. In the present report, we performed T1-weighted imaging with 2D-FLASH and T2-weighted imaging with HASTE.…”
Section: Discussionmentioning
confidence: 99%
“…2D slices from prenatal MRI have shown much less tissue contrast than that from postmortem studies [12,13]. However, these problems are being overcome with the availability of newer hardware and software allowing faster acquisition sequences such as echo-planar imaging and single-shot turbo spin echo (or HASTE) sequences [7,10] in the future. It is most likely that real-time MRI scanning will become clinically available and motion artefacts caused by fetal movement will therefore be minimized.…”
Section: Discussionmentioning
confidence: 99%